2002
DOI: 10.1007/s00251-002-0467-3
|View full text |Cite
|
Sign up to set email alerts
|

Three new human members of the lipid transfer/lipopolysaccharide binding protein family (LT/LBP)

Abstract: We have identified three novel, rarely expressed human genes that encode new members of the lipid transfer/lipopolysaccharide binding protein (LT/LBP) gene family based on sequence homology. BPI and other members of the LT/LBP family are structurally related proteins capable of binding phospholipids and lipopolysaccharides. Real-time PCR studies indicate that BPIL1 and BPIL3 are highly expressed in hypertrophic tonsils. In situ hybridization analysis of BPIL2 shows prominent expression in skin specimens from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…B is the negative control of A play an important role in adipose development. Fulllength SPLUNC1 protein was found to be structurally related to BPI, LBP, CETP, and PLTP (Guyard-Dangremont et al 1999;Mulero et al 2002;Zhou et al 2004). BPI and LBP were the bactericidal proteins and have the function of neutralizing the endotoxin.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…B is the negative control of A play an important role in adipose development. Fulllength SPLUNC1 protein was found to be structurally related to BPI, LBP, CETP, and PLTP (Guyard-Dangremont et al 1999;Mulero et al 2002;Zhou et al 2004). BPI and LBP were the bactericidal proteins and have the function of neutralizing the endotoxin.…”
Section: Resultsmentioning
confidence: 96%
“…Sequence and homology analyses suggest that SPLUNC1 is a member of the BPI/LBP family, with putative bactericidal/bacteriostatic function. Proteomics studies indicate that SPLUNC1 protein might be involved in irritant/inflammatory responses of the upper airways (Bingle and Craven 2002;LeClair 2003), the full-length SPLUNC1 protein was found to be structurally related to bactericidal permeability increasing protein (BPI), lipopolysaccharide-binding protein (LBP), cholesteryl ester transfer protein (CETP), and phospholipid transfer protein (PLTP) (Guyard-Dangremont et al 1999;Mulero et al 2002;Zhou et al 2004). BPI and LBP were the bactericidal protein and have the function of neutralizing the endotoxin.…”
Section: Introductionmentioning
confidence: 96%
“…The BPIL2 gene was found to be expressed in the basal cell layers of the epidermis in skin samples from psoriatic tissue. 88 However, little is known about the function of the BPIL2 protein. The avian homologue of the BPIL2 gene was recently shown to be highly expressed in the shell gland of mature but not of juvenile hens, pointing to a possible function in antimicrobial defence.…”
mentioning
confidence: 99%
“…Eight functional PLUNC homologues encoded in a single gene cluster on chromosome 20 in close proximity to the genes for BPI, LBP and PLTP are predicted to exist in humans. 88,90,91 The genes for the two other members, CETP and BPIL2, are located on Chromosomes 16 and 22 respectively. The PLUNC family can be divided in short (SPLUNC) and long (LPLUNC) proteins, the former consisting of only one domain corresponding to the LPSbinding N-terminal domain of BPI, the latter of two domains similar to full-length BPI.…”
mentioning
confidence: 99%
“…We obtained two nrf-5 EST cDNAs from the C. elegans Genome Project and sequenced them to determine the intron-exon boundaries of F55B12.5 (see materials and methods). Using BLAST searches, we found that NRF-5 is homologous to four mammaliansecreted lipid-binding proteins: bactericidal permeabilityincreasing (BPI) protein (Gray et al 1989;Beamer et al 1997;Beamer 2003), lipopolysaccharide-binding protein (LBP; Fenton and Golenbock 1998;Iovine et al 2002;Mulero et al 2002), cholesteryl ester transfer protein (CETP; Bruce et al 1998a;Kawano et al 2000), and phospholipid transfer protein (PLTP; Huuskonen et al 1999;Vakkilainen et al 2002). These proteins have diverse functions, but share the ability to bind various lipids.…”
Section: Resultsmentioning
confidence: 99%